2017
DOI: 10.1111/mec.14360
|View full text |Cite
|
Sign up to set email alerts
|

The roles of plasticity and evolutionary change in shaping gene expression variation in natural populations of extremophile fish

Abstract: The notorious plasticity of gene expression responses and the complexity of environmental gradients complicate the identification of adaptive differences in gene regulation among populations. We combined transcriptome analyses in nature with common-garden and exposure experiments to establish cause-effect relationships between the presence of a physiochemical stressor and expression differences, as well as to test how evolutionary change and plasticity interact to shape gene expression variation in natural sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 95 publications
1
47
1
Order By: Relevance
“…In contrast, other studies found differences in temperature responses between tropical and temperate Drosophila populations (Levine, Eckert, & Begun, 2011; von Heckel et al, 2016). Other examples for differences in genes expression plasticity between adapted and non-adapted populations include temperature (Morris et al, 2014) and salinity (Gibbons, Metzger, Healy, & Schulte, 2017; McCairns & Bernatchez, 2009) responses of marine and freshwater sticklebacks, temperature response of killifish populations from different latitudes, as well as plastic responses to toxic hydrogen sulphide (H 2 S) of fish population from H 2 S rich springs versus non-toxic springs (Passow et al, 2017). There was no consistent pattern regarding the direction in which plasticity evolves: In some cases adapted population showed an increase in plasticity (Morris et al, 2014), in other cases plasticity was reduced (Huang & Agrawal, 2016; Ragland et al, 2015; von Heckel et al, 2016) or reduction and enhancement of plasticity were equally frequent (Gibbons et al, 2017; Yampolsky et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies found differences in temperature responses between tropical and temperate Drosophila populations (Levine, Eckert, & Begun, 2011; von Heckel et al, 2016). Other examples for differences in genes expression plasticity between adapted and non-adapted populations include temperature (Morris et al, 2014) and salinity (Gibbons, Metzger, Healy, & Schulte, 2017; McCairns & Bernatchez, 2009) responses of marine and freshwater sticklebacks, temperature response of killifish populations from different latitudes, as well as plastic responses to toxic hydrogen sulphide (H 2 S) of fish population from H 2 S rich springs versus non-toxic springs (Passow et al, 2017). There was no consistent pattern regarding the direction in which plasticity evolves: In some cases adapted population showed an increase in plasticity (Morris et al, 2014), in other cases plasticity was reduced (Huang & Agrawal, 2016; Ragland et al, 2015; von Heckel et al, 2016) or reduction and enhancement of plasticity were equally frequent (Gibbons et al, 2017; Yampolsky et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how fast plasticity in gene expression can change. Some studies reported changes in plasticity in some genes after adaptation to new conditions (Morris et al, 2014; Passow et al, 2017; von Heckel, Stephan, & Hutter, 2016), whereas others found only limited evolution of plasticity (Yampolsky, Glazko, & Fry, 2012) or less than expected (Huang & Agrawal, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…However, it is important to note that physiological traits correlated with morphology may also be important. Previous studies documented significant physiological differences between fish from sulphidic and nonsulphidic populations (Passow, Arias-Rodriguez, et al, 2017a;Passow, Henpita, et al, 2017b), which may impact locomotion and ventilation. The fact that body shape cannot be the sole predictor of performance variation in our study is evidenced by the fact that we could not detect any differences in locomotion and ventilation between males and females, even though P. mexicana-like all other poeciliids (Culumber & Tobler, 2017)-exhibit pronounced sexual dimorphism.…”
Section: Functional Trade-offs and Trait-performance Correlationsmentioning
confidence: 99%
“…For example, the expression levels of CYP6AE14 and CYP6AB3, members of critical detoxifying enzyme cytochrome P450, can be induced by gossypol and furanocoumarins in lepidopterans, respectively (Mao, Rupasinghe, Zangerl, Schuler, & Berenbaum, ; Mao et al., ). Thus, the expression plasticity of key genes responding to ecological stimulation is an important force to determine the adaptation of herbivores in natural systems (Passow et al., ; Whitehead, Triant, Champlin, & Nacci, ; Yampolsky, Glazko, & Fry, ). Our data suggest that the overexpression of B. mori GII α is elicited to compensate for the inhibition of their activity by sugar‐mimic alkaloid.…”
Section: Discussionmentioning
confidence: 99%